Morphological measurements of N. abietis cocoons - Moreau, Gaétan; Eveleigh, Eldon S.; Lucarotti, Christopher J.; Morin, Benoit; Quiring, Dan T. (Dryad Digital Repository, 2017)
Fate and volume (in cubic millimeters) of Neodiprion abietis cocoons collected from 2000 to 2002 in six forest stands in western Newfoundland, Canada.